MEKANISME GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERBANKAN - Elsa Meirina; Henryanto Abaharis (JURNAL PUNDI, 2019)
This study aims to examine the mechanism of Good Corporate Governance And Leverage On Banking Financial Performance. the population is a banking company registered on the IDX in 2016, which is 43 companies. The sample collection technique has been done using a purposive sampling method and based on predetermined criteria, 8 companies have been selected as samples. The company's financial report data has been obtained from the official IDX website. The analytical method used is panel data regression analysis with the help of E-Views 8. The initial test is to test the Chow-Test to decide whether the Pooled Least Square method or Fixed Effect is used; and the Hausman-Test test to decide whether the Fixed Effect or Random Effect method can be used. The results showed that Managerial Ownership variables have a positive and not significant effect on financial performance that is proxy by ROA, the board of directors has a positive and significant effect on financial performance (ROA), leverage has a positive and not significant effect on financial performance (ROA).